The role of the compliance monitor in applying the rules of banking governance - Amir, Yasir; Nafea, Kales (Journal of Legal Sciences, 2022)
Governance system extends its application to include all internal bodies in the banking institution as well as the external authorities that impose the application of the rules of banking governance, each according to its position. Among the external actors involved in applying the rules of banking governance is the central bank that takes the position of the general supervisor of all banking activities in the country, and that the central bank exercises its supervision and control over banks through the compliance monitor, and the latter is the effective link between the central bank and the banks under its supervision. Therefore, we find that it has an important role in implementing the rules of banking governance at the level of protecting the institution and strengthening its system by preparing regulatory regulations and providing advice and suggestion through the reports submitted by it.